2016
DOI: 10.4172/jrr.1000107
|View full text |Cite
|
Sign up to set email alerts
|

By-products of Rice Processing: An Overview of Health Benefits and Applications

Abstract: Our study was centred on the increasing literature associated with rice by-products and main components, especially those intended to combat cancer, improve plasma lipid levels or control the blood glucose levels. Rice byproducts, such as rice straw, rice husks, rice bran, rice germ and broken rice, are extensively abundant agricultural wastes from the rice industry, and the percentage of their production depends on the milling rate and type of rice. Among all rice by-products, rice bran has been extensively s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 138 publications
1
24
0
1
Order By: Relevance
“…Broken rice, where starch accounts up to 87.5% of dry matter, has been adopted as a model of several agricultural and industrial wastes mainly composed by starch [9]. It is one of the most abundant waste streams of rice processing with more than 45 million tons globally produced per year [40]. Such enormous amount of cheap biomass would be directly accessible and/or collectable at rice processing sites [24].…”
Section: Of 13mentioning
confidence: 99%
“…Broken rice, where starch accounts up to 87.5% of dry matter, has been adopted as a model of several agricultural and industrial wastes mainly composed by starch [9]. It is one of the most abundant waste streams of rice processing with more than 45 million tons globally produced per year [40]. Such enormous amount of cheap biomass would be directly accessible and/or collectable at rice processing sites [24].…”
Section: Of 13mentioning
confidence: 99%
“…Lately, there has been an increase in the consumption and utilization of the byproducts of the milling process, particularly using broken kernels (Esa et al, 2013;Triratanasirichai et al, 2017). Studies have shown that rice bran, RBO, rice husk, and broken rice have potential health, animal, and alternative food uses and can be produced sustainably as they are considered renewables (Nagano et al, 2000;Ammar et al, 2012;De Godoy et al, 2013;Esa et al, 2013). Rice bran, husk, and broken rice have a variety of applications for the mechanical, food, cosmetic, agricultural, and fuel industries.…”
Section: Discussionmentioning
confidence: 99%
“…Rice bran oil is also used in baked goods as a shortening replacer because baked goods need fat and an emulsifier due to their water and fat absorption properties (Sharif et al, 2005). The quality of food is improved with the use of rice bran especially color, appearance, taste, and texture (Prakash and Ramaswamy, 1996;Esa et al, 2013;Sharif et al, 2014). The consumer concern for better health and eating habits render rice bran an optimal nutritional and dietary supplement for overall health maintenance in food use (Issara and Rawdkuen, 2017;Iriondo-DeHond et al, 2018); however, more studies are needed to provide the detailed information needed to make more specific recommendations to individual consumer requirements.…”
Section: Food Usesmentioning
confidence: 99%
See 2 more Smart Citations